Memories Come to the Surface: Pavement Memorials in Urban Public Spaces - Stevens, Quentin; Ristic, Mirjana (Journal of urban design, 2015)
Memorials installed within public pavements are a recent, distinctive genre in terms of their forms, subjects, audiences and custodianship. Through international examples, this paper examines their varied materials and designs, and their differing placement in relation to the pavement surface, the location of the events commemorated and the wider cityscape. It analyzes the particular visual and tactile encounters they frame for the passing public. These commemorative installations sit in tension with the complex ownership, regulation, use and maintenance of the public right-of-way. They also engage with specific physical and representational opportunities that the public pavement presents for commemoration.